Application of ultrasonography in neonatal lung disease: An updated review - Wang, Jin; Wei, Hongjuan; Chen, Hui; Wan, Ke; Mao, Ruifeng; Xiao, Peng; Chang, Xin (Frontiers in Pediatrics, 2022)
Lung disease is often life-threatening for both preterm and term newborns. Therefore, an accurate and rapid diagnosis of lung diseases in newborns is crucial, as management strategies differ with different etiologies. To further reduce the risk of radiation exposure derived from the conventionally used chest X-ray (CXR) as well as computed tomography (CT) scans, lung ultrasonography (LUS) has been introduced in clinical practice to identify and differentiate neonatal lung diseases, as a result of its radiation-free, convenience, high accuracy, and low-cost. In recent years, it has been proved that LUS exhibits high sensitivity and specificity for identifying various neonatal lung diseases. Here, we offer an updated review of the applications of LUS in neonatal lung diseases based on the reports published in recent years (2017 to present).